1995
DOI: 10.1002/dev.420280805
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of orientation and spatial learning on the radial maze in mices

Abstract: The development of the orientation capacities of C57BL/6 mice has been studied on the radial maze in several procedures allowed to dissociate the different types of cues used by the mouse for solving the task with two intersession delays (2 and 24 hr). The results of the first two studies show that performance is independent of intersession delay regardless of the age of the subject. Mice as early as 23 days old obtain good performances when they can develop an algorithmic strategy or when they dispose of both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 28 publications
3
24
1
Order By: Relevance
“…However, while we have already demonstrated (Chapillon et al, 1995) that the working memory in 23-day-old mice is totally functional, other studies have also shown that in simple tasks (Nagy, Misanin, Newman, Olsen, & Hinderliter, & Sandmann, 1973) the working memory of mice is functional as early as 9 days of age. The working-memory versus reference-memory hypothesis thus seems irrelevant to explain the contradiction.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…However, while we have already demonstrated (Chapillon et al, 1995) that the working memory in 23-day-old mice is totally functional, other studies have also shown that in simple tasks (Nagy, Misanin, Newman, Olsen, & Hinderliter, & Sandmann, 1973) the working memory of mice is functional as early as 9 days of age. The working-memory versus reference-memory hypothesis thus seems irrelevant to explain the contradiction.…”
Section: Discussionmentioning
confidence: 86%
“…In this study, contrary to adults, the younger mice perform better with more compactly grouped sessions. The results of another experiment on a radial maze (Chapillon et al, 1995) have shown that, in this other type of spatial learning, younger mice also obtain better performances when the training sessions are closely grouped. Whatever the reason, the results shown by the younger mice on the Morris test demonstrate the excellent navigational capacity of very young animals.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations